Some challenges, principles and applications of the connected learning approach - Moises Esteban-Guitart; Daniela K. DiGiacomo; William R. Penuel; Mizuko Ito (Universidad de La Rioja, 2020)
Connected learning refers to an activity, practice, or experience that brings together youth interests and learning with academic, career, and/or civic related opportunities - and is supported by and through peer interaction. The fundamental purpose of this article is to situate the approach of connected learning, both in theory and practice. To do so, we describe its origins and underlying theoretical principles, as well as the requisite social and material conditions to instantiate a connected learning approach in educational settings in ways that enable the promotion of relational equity. In closing, we offer some examples of connected learning in practice, as well as some of what we consider to be its current limitations and design and implementation challenges.